A Granular Thermodynamic Model to Describe the Temperature/Mechanical Characteristics of Sandy Soil - Zhou, Rui; Gao, Siyuan; Wang, Wei (Frontiers in Earth Science, 2021)
Based on the granular-solid-hydrodynamic theory, the constitutive model considering the thermo-hydro-mechanical coupling action is established, and the dilatancy property of sandy soil under coupled high mechanical pressure and temperature is simulated. The relationship between the energy dissipation and the macroscopic stress-strain changes at the grain level of saturated sand is connected by defining the transfer coefficient and the energy function, without considering the concepts of yield surface and hardening parameters in classical plastic mechanics. Additionally, the changes in temperature, relative density and confining pressure during the shearing process cause particle rolling, slipping and friction. The energy dissipation in this process is described by defining the concept of particle entropy and particle temperature. In the calculation, the isotropic compression test, drained and undrained shear test of sand under high stress are simulated respectively. The validity of the model is proved by comparing with the test results. Meanwhile, the stress-strain relationship and pore pressure variation law of sand under different temperatures are predicted. The results show that the effect of temperature on shear strength is limited, and the pore pressure will gradually increase and become stable with the increase of temperature. Thus, this work establishes the soil THM coupling model from the perspective of micro energy dissipation, which can provide new theoretical support for the prediction of natural disasters such as landslides and debris flow.